SISTEM PENGKADERAN BERORGANISASI SANTRI (Studi Kasus di Pesantren Maslakul Huda Kajen Margoyoso Pati Jawa Tengah) (JPP, 2011)
Education in Islamic boarding school has always been an interesting discourse to bestudied, discussed and researched. Islamic traditional educational institute that has beenentrenched in this society is largely managed traditionally. Nevertheless, boarding schoolstill get the recognition and trust from the community, because the boarding school cangrow the values of sincerity, self-sufficient, simplicity, fraternity, brotherhood, and freedom.This research purposes to uncover management of cadre by Presidium System inMaslakul Huda Islamic boarding School Kajen Margoyoso Pati Central Java.The results indicated that the implementation of organizational learning process inMaslakul Huda Islamic Boarding School, Kajen Margoyoso Central Java Pati is alreadyapplying the principles of management of cadre organization. Management of cadre organizationapplied in three forms: (1) cadre planning by presidium system, (2) cadre implementationby presidium system, and (3) cadre evaluation by presidium system. Somedata which are relating the structure and mechanism of organization, work programs, andinfrastructure, can be used as argument reference that management of cadre has been implementedin the whole of the school organizational learning programs.Keyword: management of cadre, Presidium System